Potential Role of mRNAs and LncRNAs in Chronic Intermittent Hypoxia Exposure-Aggravated Atherosclerosis - Zhang, Jing; Hu, Chaowei; Jiao, Xiaolu; Yang, Yunyun; Li, Juan; Yu, Huahui; Qin, Yanwen; Wei, Yongxiang (Frontiers in Genetics, 2020)
Atherosclerosis is the pathological basis of cardiovascular disease. Obstructive sleep apnea (OSA) aggravates atherosclerosis, and chronic intermittent hypoxia (CIH) as a prominent feature of OSA plays an important role during the process of atherosclerosis. The mechanisms of CIH in the development of atherosclerosis remain unclear. In the current study, we used microarray to investigate differentially expressed mRNAs and long non-coding RNAs (lncRNAs) in aorta from five groups of ApoE–/– mice fed with a high-fat diet and exposed to various conditions: normoxia for 8 weeks, CIH for 8 weeks, normoxia for 12 weeks, CIH for 12 weeks, or CIH for 8 weeks followed by normoxia for 4 weeks. Selected transcripts were validated in aorta tissues and RT-qPCR analysis showed correlation with the microarray data. Gene Ontology analysis and pathway enrichment analysis were performed to explore the mRNA function. Bioinformatic analysis indicated that short-term CIH induced up-regulated mRNAs involved in inflammatory response. Pathway enrichment analysis of lncRNA co-localized mRNAs and lncRNA co-expressed mRNAs were performed to explore lncRNA functions. The up-regulated mRNAs, lncRNA co-localized mRNAs and lncRNA co-expressed mRNAs were significantly associated with protein processing in endoplasmic reticulum pathway in atherosclerotic vascular tissue with long-term CIH exposure, suggesting that differentially expressed mRNAs and lncRNAs play important roles in this pathway. Moreover, a mRNA-lncRNA co-expression network with 380 lncRNAs, 508 mRNAs and 3238 relationships was constructed based on the correlation analysis between the differentially expressed mRNAs and lncRNAs. In summary, our study provided a systematic perspective on the potential function of mRNAs and lncRNAs in CIH-aggravated atherosclerosis, and may provide novel molecular candidates for future investigation on atherosclerosis exposed to CIH.